Heart Rate Variability and Risk of All-Cause Death and Cardiovascular Events in Patients With Cardiovascular Disease: A Meta-Analysis of Cohort Studies. Issue 1 (January 2020) - Fang, Su-Chen; Wu, Yu-Lin; Tsai, Pei-Shan
Lower heart rate variability (HRV) is associated with a higher risk of cardiovascular events and mortality, although the extent of the association is uncertain. We performed a meta-analysis of cohort studies to elucidate the association between HRV and the risk of all-cause death or cardiovascular events in patients with cardiovascular disease (CVD) during a follow-up of at least 1 year. We searched four databases (PubMed, MEDLINE, Embase, and Cochrane Central Register of Controlled Trials) and extracted the adjusted hazard ratio (HR) from eligible studies. We included 28 cohort studies involving 3, 094 participants in the meta-analysis. Results revealed that lower HRV was associated with a higher risk of all-cause death and cardiovascular events; the pooled HRs were 2.12 (95% confidence interval [CI] = [1.64, 2.75]) and 1.46 (95% CI [1.19, 1.77]), respectively. In subgroup analyses, the pooled HR of all-cause death was significant for patients with acute myocardial infarction (AMI) but not for those with heart failure. The pooled HR for cardiovascular events was significant for the subgroup of patients with AMI and acute coronary syndrome but not for those with coronary artery disease and heart failure. Additionally, both time and frequency domains of HRV were significantly associated with risk of all-cause death and cardiovascular events in patients with CVD.